2015
DOI: 10.1017/s0007114515004146
|View full text |Cite
|
Sign up to set email alerts
|

Folate, vitamin B6, vitamin B12 and methionine intakes and risk for nasopharyngeal carcinoma in Chinese adults: a matched case–control study

Abstract: Many studies have suggested that folate-related one-carbon metabolism-related nutrients may play a role in certain cancer risks, but few studies have assessed their associations with the risk for nasopharyngeal carcinoma (NPC). In this study, we investigated the association between four folate-related one-carbon metabolism-related nutrients (folate, vitamin B 6 , vitamin B 12 and methionine) and NPC risk in Chinese adults. A total of 600 patients newly diagnosed (within 3 months) with NPC were individually mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
2
16
1
1
Order By: Relevance
“…Folic acid (FA), a fully oxidized monoglutamyl form of folate, is frequently used as nutritional supplement for folate, since it is more stable and its bioavailability as compared with folate [ 7 ]. It is reported that dietary FA intake is protective for NPC in a high-risk population of Chinese adults [ 8 ]. Folate receptor α (FRα), a single chain glycosyl-phosphatidylinositol-anchored membrane protein, is the major transporter of FA and acts as an important mediator in many cancers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Folic acid (FA), a fully oxidized monoglutamyl form of folate, is frequently used as nutritional supplement for folate, since it is more stable and its bioavailability as compared with folate [ 7 ]. It is reported that dietary FA intake is protective for NPC in a high-risk population of Chinese adults [ 8 ]. Folate receptor α (FRα), a single chain glycosyl-phosphatidylinositol-anchored membrane protein, is the major transporter of FA and acts as an important mediator in many cancers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The included main studies were conducted in Europe (n = 5), [ 18 , 21 , 28 30 ] and others were conducted in Asia (n = 2), [ 20 , 31 ] North America (n = 1), [ 19 ] and South America (n = 1). [ 32 ] Among the 9 included studies, 3 studies involved patients with comprehensive HNSCC, [ 19 21 ] 3 studies involved patients with laryngeal cancer, [ 18 , 29 , 32 ] 2 studies involved patients with nasopharyngeal carcinoma, [ 30 , 31 ] and 1 study involved patients with oral cavity and pharyngeal squamous cell carcinoma (OPSCC). [ 28 ] Seven studies investigated the associations between dietary folate intake and HNSCC risk.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 , 21 ] In terms of source of control, 7 studies were hospital-based [ 18 , 28 32 ] and 2 studies were population-based. [ 19 , 21 ] Five studies matched high score with NOS scale, [ 18 21 , 31 ] and 4 studies matched low score. [ 28 30 , 32 ] Four studies were included in dose–response analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Folate, vitamin B6 (B6), and vitamin B12 (B12) have been proven to play important roles in the one-carbon metabolism pathway and the prevention of carcinogenesis: (a) in the transformation of homocysteine (Hcy) to methionine for methylation of DNA to ensure gene expression and genomic stability; and (b) in the synthesis of purine precursors and thymidylate of nucleic acid (DNA and RNA) [ 1 , 2 , 3 , 4 ]. B6 is not only a crucial coenzyme for serine hydroxymethyltransferase (SHMT) in the reversible transformation of serine and tetrahydrofolate (THF) to 5,10-methylene THF and glycine [ 5 , 6 ], a reaction that offers one-carbon units for S-adenosylmethionine (SAM), and for the synthesis of purine and pyrimidine, but it is also a cofactor for cystathionine β-synthase (CBS), which is involved in the transsulfuration pathway where Hcy is converted into cystathionine.…”
Section: Introductionmentioning
confidence: 99%